Effect of theophylline on airway inflammation in asthma - Yang Jiong; Tu Hai-Yan; Li Qing-Quan (Acta Pharmacologica Sinica, 2016)
Aim: To investigate whether low dose theophylline has an anti-inflammatory effect in asthma. Methods: Nineteen asthmatic subjects were given 200 mg sustained-release theophylline preparation twice daily for 4 weeks. The mean serum concentration of theophylline was 7.9 mg/L. The percentage of eosinophils, EG2+ eosinophils, and the level of eosinophil cationic protein (ECP) in sputum pre- and post-administration were detected by Wright's stain, immunocytochemistry, and immuno-CAP system, and the symptom scores and lung function were evaluated as well. The above indices for 10 healthy subjects were regarded as control. Results: Before using theophylline, sputum eosinophils, EG2+ eosinophils, and ECP in asthmatic group were much higher than those of healthy group. After four weeks administration, there were great decreases in percentage of total eosinophils (40 % +/- 17 % vs 29 % +/- 11 %, P < 0.01), activated (EG2+) eosinophils (28 % +/- 9 % vs 10 % +/- 8 %, P < 0.01) and in the concentration of sputum ECP [(373 +/- 206) vs (220 +/- 132) microg/L, P < 0.01]. The symptom scores decreased greatly (7.1 +/- 1.2 vs 5.4 +/- 1.6, P < 0.01). There was a marked increased in forced expiratory volume one second (FEV(1.0)) after administration (2.2 +/- 0.6 vs 2.4 +/- 0.5, P < 0.01). The FEV(1.0) % of asthmatic subjects after administration increased (60 % +/- 13 % vs 65 % +/- 13 %, P < 0.01), too. Conclusion: These results indicated that low dose theophylline had inhibitory action on airway inflammation in asthma with noticeable improvement of the patients' symptoms and lung function.